Sales Behavioral Intentions of Distribution Channels in the Insurance Industry : A Systematic Review - Shetty, Ankitha; Basri, Savitha (Indian Journal of Marketing, 2017)
The convoluted nature of insurance products promotes information asymmetry ensuing unethical behaviour of insurance agents. A systematic review of the sales behavioral intentions of agents will provide valuable insights into the issues of specious agent behavior. To the best of our knowledge, this study is the first that employed a systematic literature review with the objective to identify the variables that determine ethical or unethical behaviour and explicated its pattern amongst the agents of insurance companies. This study revealed that the behavioual intentions primarily depend upon the attitude, subjective norm, and perceived behavioural control. Loss of income, fear of losing a job, and lucrative incentives offered by insurance companies motivate agents to push the products by engaging in unscrupulous practices that violate the ethical norms. Hence, the sales managers should uphold a high moral attitude among sales agents, foster a diminution in unethical behaviour, and also provide extensive ethics training for establishing and maintaining long-term relationships with their customers to accomplish long-term profitability.